Open and Nimble : Finding Stable Growth in Small Economies - Lederman, Daniel; Lesniak, Justin T. (Washington, DC: World Bank, 2017)
Does economic size matter for economic development outcomes? If so are current policies adequately addressing the role of size in the development process? Using working age population as a proxy for country size, Open and Nimble, systematically analyzes what makes small economies unique.